2012
DOI: 10.4102/sajhrm.v10i2.419
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the self-esteem and employability attributes of postgraduate business management students

Abstract: <strong>Orientation:</strong> The effects of challenges (like decreased employment opportunities, increased personal responsibility to keep up with changes, current skill shortages and of retaining talented and skilled staff) have led to an emphasis on career meta-competencies to improve employability attributes.<p><strong>Research purpose:</strong> The objectives of the study were to determine the relationship between self-esteem (as the Culture Free Self-Esteem Inventory measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 49 publications
(89 reference statements)
1
30
0
Order By: Relevance
“…It reflects and affects their dealings with the environment and the people with whom they come into contact (Kernis, 2003). Potgieter, (2012), confirmed that career meta-competencies such as self-esteem, do influence employability attribute significantly. Hence, career development support practices and career counselling interventions could be exploited from anyone who wants to reinforce his employability.…”
Section: Self Esteemmentioning
confidence: 72%
“…It reflects and affects their dealings with the environment and the people with whom they come into contact (Kernis, 2003). Potgieter, (2012), confirmed that career meta-competencies such as self-esteem, do influence employability attribute significantly. Hence, career development support practices and career counselling interventions could be exploited from anyone who wants to reinforce his employability.…”
Section: Self Esteemmentioning
confidence: 72%
“…It is even suggested that the whole notion of ability has been extended to embrace a set of skills habitually indistinguishable from personal characteristics, behaviours and attitudes, which in the past would rarely have been regarded as abilities at all (Payne 2000;Potgieter 2012). Accordingly, the concept of ability is also used as a generic notion in the present study, referring both to capabilities (e.g.…”
Section: Employability and Perceived Abilitiesmentioning
confidence: 96%
“…While the dimensions of ability self tended to reflect in students' employability perceptions, it is likely that they play a role during their studies and in the ways students deal with challenging study phases such as MA thesis work. There is also research evidence to show that self-perceived employability increases feelings of being in control of one's career (Potgieter 2012). Accordingly, we are basically dealing with students' self-confidence and learner's identity.…”
Section: Policy and Educational Implicationsmentioning
confidence: 99%
“…There is also broad acknowledgement and documented evidence that career management influences individual employability (Potgieter 2012;Raemdonck et al 2011) and 'how the individual perceives his or her opportunities in the labour market' (Berntson and Marklund 2007, 281). There is evidence, although Bridgstock (2009) argues somewhat limited, that skills in accessing and using relevant information on career roles, job applications and labour markets will positively impact on employment outcomes (Krug and Rebien 2011;Pegg et al 2012).…”
Section: The Importance Of Career Management Competenciesmentioning
confidence: 99%